Locus-Specific Proteomics by TChP: Targeted Chromatin Purification - Farzin Pourfarzad; Ali Aghajanirefah; Ernie de Boer; Sara Ten Have; Thamar Bryn van Dijk; Sima Kheradmandkia; Ralph Stadhouders; Supat Thongjuea; Eric Soler; Nynke Gillemans; Marieke von Lindern; Jeroen Demmers; et al. (Cell Reports, 2013)
Here, we show that transcription factors bound to regulatory sequences can be identified by purifying these unique sequences directly from mammalian cells in vivo. Using targeted chromatin purification (TChP), a double-pull-down strategy with a tetracycline-sensitive “hook” bound to a specific promoter, we identify transcription factors bound to the repressed γ-globin gene-associated regulatory regions. After validation of the binding, we show that, in human primary erythroid cells, knockdown of a number of these transcription factors induces γ-globin gene expression. Reactivation of γ-globin gene expression ameliorates the symptoms of β-thalassemia and sickle cell disease, and these factors provide potential targets for the development of therapeutics for treating these patients.